Does gender influence farm households’ decision to adopt technology and commercial agriculture: Implication for household food security in rural Bangladesh (SAARC Journal of Agriculture, 2019)
This paper investigates whether gender of household head is associated with the household’s decision to adopt technology and commercial agriculture in rural Bangladesh. It further investigates if household food security of the adopters differs significantly on the basis of gender of the household head. By using Ӽ2 test and Cramer’s V statistic this paper finds evidence to suggest that adoption of both technology and of commercialisation of agriculture in rural Bangladesh significantly differs between male-headed and female-headed households. The incidence of adoption among the female-led households is low possibly because they are constrained by lack of access to input, credit, and extension services. It is also found that household food security of the adopters improves irrespective of gender of the household head. Thus the policy implication of the study is that technology adoption and commercial farming may have good prospect for improving household food security of rural farm households.SAARC J. Agri., 17(1): 219-226 (2019)